Greenness of procedures using NADES in the preparation of vegetal samples: Comparison of five green metrics - Ferreira, Sabrina S. [UNESP]; Brito, Thomas A. [UNESP]; Santana, Ana P. R.; Guimaraes, Taciana G. S.; Lamarca, Rafaela S. [UNESP]; Ferreira, Karen C. [UNESP]; Gomes, Paulo C. F. Lima [UNESP]; Oliveira, Andrea; Amaral, Clarice D. B.; Gonzalez, Mario H. [UNESP] (Elsevier B.V., 2022)
The principles of green analytical chemistry have led to the development of analytical procedures that are increasingly sustainable. Different metrics have been created for the evaluation of greenness, although determination of the green nature of new analytical methods remains challenging, including for extraction methods that involve the use of natural deep eutectic solvents (NADES). In this study, the following five chemical metrics for the evaluation of greenness were considered: National Environmental Methods Index (NEMI), Green Analytical Procedure Index (GAPI), Analytical Eco-Scale, Analytical GREEnness (AGREE), and White Analytical Chemistry (WAC). These methods were applied in evaluation of the environmental and sustainability characteristics of three different methods for the preparation of plant material samples: microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), and microwave-assisted acid digestion (MW-AD). These methods employed different NADES as extraction solvents, as well as dilute nitric acid as an oxidizing agent, for the determination of As, Cd, Pb, and V by inductively coupled plasma mass spectrometry (ICP-MS). The NEMI metric found no differences between the MAE-NADES and UAE-NADES methods. The GAPI metric found differences between the MAE-NADES and UAE-NADES methods and identify the disadvantageous aspects of each step of the methods. The Analytical Eco-Scale and AGREE identified the MAE-NADES method as the greenest, while WAC-12 RGB indicated the UAE-NADES method as the greenest procedure. A detailed discussion is provided of the application of each metric, together with their differences and advantages.
Keywords: Natural deep eutectic solvent (NADES); National environmental methods index (NEMI); Green analytical procedure index (GAPI); Analytical Eco-scale; Analytical GREEnness (AGREE); White analytical chemistry (WAC)